Konteks Produksi Ditinjau Dari Maqashid Al-Syariah - Nani Nani; Nordiyana Binti Nordin (PROGRAM STUDI EKONOMI ISLAM PROGRAM PASCASARJANA IAIN SULTAN MAULANA HASANUDDIN BANTEN, 2023)
Production has an important role in the process of economic activity in meeting human needs. In theory, human needs are not limited, while the means of satisfying needs are limited, so they need to be accompanied by good stages in production according to Islamic teachings. The purpose of this study is to analyze the implementation of maqashid Al sharia in good and correct production activities according to Islamic teachings, namely guided by the Al-Qur'an and Hadith. This research is a qualitative research with a descriptive approach. The data collection technique is using the method of documentation and literature study. The research results obtained are that the production context in terms of maqashid Al sharia has motives for benefit, needs and obligations so that the production principle must be based on Islamic values ​​and production priorities must be in accordance with the stages of human needs, namely starting from dharuriyyat, then hajyiyat and finally tahsiniyat. This is so that needs and desires are not mixed and can be wisely fulfilled properly. In fulfilling maqashid Al sharia in production activities, there are several points that need to be considered. These important points are maintaining the halal raw materials and tools used, avoiding hazardous materials for health, not presenting things that are intoxicating or damaging to the mind either in the form of food or broadcasts, avoiding over-exploitation of natural resources, not monopolizing the market, not playing the price and not intentionally pressing money so that it only goes to certain parties.